Altered Brain Cholesterol/Isoprenoid Metabolism in a Rat Model of Autism Spectrum Disorders. (21st February 2018) - Cartocci, Veronica; Catallo, Martina; Tempestilli, Massimo; Segatto, Marco; Pfrieger, Frank W.; Bronzuoli, Maria Rosanna; Scuderi, Caterina; Servadio, Michela; Trezza, Viviana; Pallottini, Valentina
Highlights: Modification of cholesterol/isoprenoid homeostasis in brain regions of rats prenatally exposed to valproic acid. In valproic acid-exposed rats, HMGCR modulation depends principally on AMPK activation. Altered prenylation in cerebellum and nucleus accumbens of rats prenatally exposed to valproic acid. Hippocampal oligodendrocytes are reduced in rats prenatally exposed to valproic acid. Abstract: Autism spectrum disorders (ASDs) present a wide range of symptoms characterized by altered sociability, compromised communication and stereotypic/repetitive behaviors. These symptoms are caused by developmental changes, but the mechanisms remain largely unknown. Some lines of evidence suggest an impairment of the cholesterol/isoprenoid metabolism in the brain as a possible cause, but systematic analyses in rodent models of ASDs are lacking. Prenatal exposure to the antiepileptic drug valproate (VPA) is a risk factor for ASDs in humans and generates a well-established model for the disease in rodents. Here, we studied cholesterol/isoprenoid metabolism in different brain areas of infant, adolescent and adult rats prenatally exposed to VPA. VPA-treated rats present autistic-like symptoms, they show changes in cholesterol/isoprenoid homeostasis in some brain areas, a decreased number of oligodendrocytes and impaired myelination in the hippocampus. Together, our data suggest a relation between brain cholesterol/isoprenoid homeostasis and ASDs.